A Case Study to Dissect Immunity to SARS-CoV-2 in a Neonate Nonhuman Primate Model - Fovet, Claire-Maëlle; Pimienta, Camille; Galhaut, Mathilde; Relouzat, Francis; Nunez, Natalia; Cavarelli, Mariangela; Sconosciuti, Quentin; Dhooge, Nina; Marzinotto, Ilaria; Lampasona, Vito; Tolazzi, Monica; Scarlatti, Gabriella; et al. (Frontiers in Immunology, 2022)
Most children are less severely affected by coronavirus-induced disease 2019 (COVID-19) than adults, and thus more difficult to study progressively. Here, we provide a neonatal nonhuman primate (NHP) deep analysis of early immune responses to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in blood and mucosal tissues. In addition, we provide a comparison with SARS-CoV-2-infected adult NHP. Infection of the neonate resulted in a mild disease compared with adult NHPs that develop, in most cases, moderate lung lesions. In concomitance with the viral RNA load increase, we observed the development of an early innate response in the blood, as demonstrated by RNA sequencing, flow cytometry, and cytokine longitudinal data analyses. This response included the presence of an antiviral type-I IFN gene signature, a persistent and lasting NKT cell population, a balanced peripheral and mucosal IFN-γ/IL-10 cytokine response, and an increase in B cells that was accompanied with anti-SARS-CoV-2 antibody response. Viral kinetics and immune responses coincided with changes in the microbiota profile composition in the pharyngeal and rectal mucosae. In the mother, viral RNA loads were close to the quantification limit, despite the very close contact with SARS-CoV-2-exposed neonate. This pilot study demonstrates that neonatal NHPs are a relevant model for pediatric SARS-CoV-2 infection, permitting insights into the early steps of anti-SARS-CoV-2 immune responses in infants.